Types of misrepresentation in English law and compensation resulting from it - الساعدي, جليل حسن; خلف, هند عباس (Journal of Legal Sciences, 2021)
English law defines different types of fraud, and we do not find a counterpart in other legislations, relying on its distinction on the criterion of knowledge of the truth of the information presented, that is, determining the type of fraud depends on the extent of the owner of false evidence that it is not correct at the time of its issuance. These false statements are either issued from Accompanying the owner with his full knowledge of its content and in a way that makes it a presumption that proves his bad intention so that fraud is not innocent, or that it is issued by indiscretion and negligence and without a reasonable and logical basis on which it is based, then fraud is negligently, and finally that this data is issued by its owner and he believes its validity, i.e. that it is based on evidence Statement to the foundations of M. Reasonable and reasonable enough to believe that the statement was correct, so fraud is innocent, And these types represent the positive act of misrepresentation, and the negative act for it is achieved by concealing the representor information about the contract from the representee, with the intention of prompting him to contract.